The Role and Legal Basis of Ethical-Psychology in Working with Citizens During the Service of the Employees of the Internal Affairs Bodies (Journal of Pedagogical Inventions and Practices, 2022)
Organization of moral-psychological units in the field in order to increase the moralpsychological awareness of the employees of internal affairs bodies.